RESERVOIR PROPERTIES OF THE GUA MUSANG FORMATION (MIDDLE PERMIAN – MIDDLE TRIASSIC) NEAR POS BLAU, ULU KELANTAN - YUSOH, SUHAIDEE (Universiti Teknologi PETRONAS, 2015)
The deepwater depositional system is the one type of reservoir system that cannot be easily reached, directly observed and studied in the modern environment. To study the deepwater depositional system, an exposure onshore outcrop is a good paradigm to focus on reservoir system. Thus, for this project, outcrops of the Gua Musang formation (Middle Permian to Middle Triassic) along the Cameron Highland-Gua Musang road near Pos Blau were studied. Two outcrops consist of conglomerate sandstone and very fine-grained chert. This project is aim to enhance general understanding of reservoir properties of the Gua Musang formation using the available data and the aids of stratigraphy study. Structure and Laboratory analysis such as Stereonet, Rose Diagram, Thin section, Thermal Conductivity and Mercury Porosity analysis are conducted in order to discuss the depositional environment of the study area. Porosity can be determined to describe the analogue reservoir properties of the Gua Musang formation. This can be done through analyzing the textural, mineralogical maturity and burial history.